Teachers' Knowledge of Integrating Mobile Applications into Teaching Listening to Adult Learners in an English Course - Sabrina, Rizqi; Basikin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates teachers' knowledge and challenges in utilizing mobile applications in listening instructions for adult learners. The research employs a qualitative method with a case study approach, employing single data collected at the Jogja English Training Centre (JETC) in Yogyakarta, Indonesia. Data was collected through a questionnaire including closed-ended and open-ended questions to obtain insights into teachers' confidence, familiarity, and pedagogical comprehension of mobile applications for teaching listening. Findings show that teachers have a strong knowledge of integrating mobile applications. They mix traditional methods with mobile tools and keep themselves updated with the latest technological enhancements. However, teachers still need professional development in monitoring students' progress. This research highlights the potential of teachers' knowledge of mobile applications to develop students' listening skills. It is suggested that teachers get training to maximize the utilization of mobile applications. The limitation of the study is the dependency on a single data source, reinforcing future research by incorporating a variety of data to get a more comprehensive analysis